2010
DOI: 10.3390/ijerph7031076
|View full text |Cite
|
Sign up to set email alerts
|

A New View of Alcohol Metabolism and Alcoholism—Role of the High-Km Class Ⅲ Alcohol Dehydrogenase (ADH3)

Abstract: The conventional view is that alcohol metabolism is carried out by ADH1 (Class I) in the liver. However, it has been suggested that another pathway plays an important role in alcohol metabolism, especially when the level of blood ethanol is high or when drinking is chronic. Over the past three decades, vigorous attempts to identify the enzyme responsible for the non-ADH1 pathway have focused on the microsomal ethanol oxidizing system (MEOS) and catalase, but have failed to clarify their roles in systemic alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 64 publications
(95 reference statements)
2
36
1
1
Order By: Relevance
“…In particular, ADH3 (the isoform belonging to class III according to the old nomenclature may participate to ethanol metabolism together with ADH1 or compensating for its reduced contribution (Haseba et al, 2003). In addition, it was suggested that chronic binge drinking might shift the key metabolic pathway from ADH1 to ADH3 (Haseba and Ohno, 2010), therefore attributing ADH3 a more critical role at high ethanol concentrations. Notably, 4-MP inhibits ADH1 but not ADH3 (Haseba and Ohno, 1997).…”
Section: Peripheral Generation Of Acetaldehydementioning
confidence: 99%
“…In particular, ADH3 (the isoform belonging to class III according to the old nomenclature may participate to ethanol metabolism together with ADH1 or compensating for its reduced contribution (Haseba et al, 2003). In addition, it was suggested that chronic binge drinking might shift the key metabolic pathway from ADH1 to ADH3 (Haseba and Ohno, 2010), therefore attributing ADH3 a more critical role at high ethanol concentrations. Notably, 4-MP inhibits ADH1 but not ADH3 (Haseba and Ohno, 1997).…”
Section: Peripheral Generation Of Acetaldehydementioning
confidence: 99%
“…Following parenteral administration of ethanol, these mice displayed an increased sleep time and embryonic resorption was increased 3-fold [9]. While ADH1 is thought to be responsible for the majority of ethanol metabolism in the liver, new pharmacokinetic evidence suggests a role for other ADH isoforms as well [48]. Therefore, this model may be useful in determining the pathophysiological importance of compensatory ADH isoforms as well as elucidating the kinetics of these enzymes for ethanol.…”
Section: Mouse Models With Genetic Deficiencies In Ethanol-metabolmentioning
confidence: 99%
“…A plausible explanation is that chronic exposure to ethanol leads to hyperinsulinemia [125], which shifts energy supply from glucose to ketone bodies [65]. In turn, high ketone bodies alongside oxidized carbohydrates and iron overload shift ethanol metabolism from low Km ADH1 (that works in the millimolar range) to high Km alcohol-metabolizing enzymes (that work in the molar range) [65,141] such as cytochrome P450 2E1 (CYP2E1), ADH4, and ADH3 [28,30,66,69,126,142,143]. The net result is that large amounts of ethanol may cause organ damage concurrently with negligible BACs (Figure 2) [28,30,[65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%